Global visualization of adolescent idiopathic scoliosis treatment: a bibliometric analysis - Zheng, Xiaodong; Han, Wenjin; Gao, Shan; Jia, MengLong; Liu, LiJun; Yu, Longtan (Frontiers in Pediatrics, 2025)
ObjectiveThe objective of this study is to present a comprehensive overview of current advancements, prominent areas of interest, emerging trends, and frontiers in global research concerning the treatment of adolescent idiopathic scoliosis. The aim is to offer valuable insights and guidance for future research endeavors in this field.MethodsWe conducted a literature search on the treatment of adolescent idiopathic scoliosis using the Web of Science Core Collection database spanning from 2009 to 2024. Visualization of countries, institutions, authors, and keywords was performed using CiteSpace.Results1,002 English articles were included in this study. Between 2009 and 2020, publications remained relatively low and stable. However, in 2021, interest in the treatment of adolescent idiopathic scoliosis began to surge, a noticeable increase in publications, with a peak reached in 2022. The United States emerged as the leading contributor among countries, institutions, and authors. Nanjing University and Peter O. Newton were the most prolific institutions and authors, respectively. The academic journal with the highest number of published articles was Spine. Notably, areas such as Cobb angle measurement, the efficacy of non-surgical treatments for AIS, and factors influencing the success of brace treatment garnered significant attention as hot topics in adolescent idiopathic scoliosis treatment.ConclusionThe prognosis remains consistent across patients with varying degrees of curvature in adolescent idiopathic scoliosis. Given the limited understanding of its etiology, the relationship between curvature and prognosis, as well as the exploration of its underlying causes, could emerge as new research directions in the future.